Pengaruh penggunaan air kelapa terhadap pertumbuhan kangkung darat (Ipomoea reptans Poir) - Damarce Trimartin Robeka Awairaro; Hangrie Jimmy Namserna; Veronica Leonora Tuhumena; Fenny Salomina Jensaura Asyerem; Rizald Hussein (Fakultas Pertanian Universitas Papua, 2020)
This research was conducted to determine the most effective concentration of young coconut water to increase the growth of land kangkung. This study used a regression analysis design, with 15 coconut water concentration treatments, namely: 0%; 7.14%, 14.28 %, 21.42 %, 28.56 %, 35.70 %, 42.84 %, 48.98 %, 57.12 %, 64.26 %, 71.40%, 78.54%, 85.68%, 92.82%, and 99.96%. The variables observed in this study included plant height, number of leaves, leaf area, fresh weight, and dry weight. The data were analyzed using linear regression to see the effect of coconut water concentration on the growth of land kangkung plants from 15 treatments. The results of the study found that the application of coconut water at various concentrations had a significant but negative effect on plant height at 2 and 6 week, number of leaves at 2 week, leaf area at 2 week, as well as wet weight and dry weight of plants at age 6 week.